2021
DOI: 10.3390/ijerph182211920
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual Well-Being for Croatian Cancer Patients: Validation and Applicability of the Croatian Version of the EORTC QLQ-SWB32

Abstract: Spiritual well-being is a recognized predictor of health-related quality of life in palliative patients. No research in Croatia has yet addressed this field. This study, the first of its kind in Croatia, validated a Croatian translation of the EORTC QLQ-SWB32 measure of spiritual well-being with curative Croatian oncology patients and assessed its use and value. The study was conducted between July 2019 and January 2020 at the Department of Radiotherapy and Oncology, University Hospital Rijeka, with 143 cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
13
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 32 publications
6
13
4
Order By: Relevance
“…Meanwhile, sentence I8, "I feel able to share thoughts about life with people close to me," had the strongest loading in EX (0.371), and the factor loading in the RO group was less strong (0.323). Our research results contrasted with those of previous studies, showing the strongest factor loading of I8 in the RO group and being less strong in the EX group [16,25]. The emotional state of cancer patients during this time could be observed.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Meanwhile, sentence I8, "I feel able to share thoughts about life with people close to me," had the strongest loading in EX (0.371), and the factor loading in the RO group was less strong (0.323). Our research results contrasted with those of previous studies, showing the strongest factor loading of I8 in the RO group and being less strong in the EX group [16,25]. The emotional state of cancer patients during this time could be observed.…”
Section: Discussioncontrasting
confidence: 99%
“…We found that this measurement was easy to understand and accepted by patients, being used to quantify SWB widely in Vietnam. The results were similar to other studies around the world [16,25].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations